Face mask uptake in the absence of mandates during the COVID-19 pandemic: a qualitative interview study with Swiss residents - Bettina Maria Zimmermann; Johanna Eichinger; Franziska Schönweitz; Alena Buyx (BMC, 2021)
Abstract Background In the COVID-19 pandemic, Switzerland introduced broad nationwide face mask mandates only by October 2020, later than other Western European countries. This study aims to assess the underlying values and considerations of individuals to wear face masks in the absence of face mask mandates in the COVID-19 pandemic in German-speaking Switzerland. Methods As part of the "Solidarity in times of a pandemic" (SolPan) research commons, we interviewed 31 participants living in the German-speaking part of Switzerland in April 2020 and 25 of them again in October 2020. Qualitative inductive thematic analysis was applied for data analysis and interpretation. Public health ethics principles guided the interpretation and organization of findings. Results Five themes were identified: Trust and governmental policy; perceived benefits of mask-wearing; perceived risks of mask-wearing; social exclusion and prejudice; and decision-making in the absence of mandates. In light of increasing infection rates in October 2020, many participants started to consider the benefits higher than the risks and were willing to accept face mask mandates in that context, despite earlier reservations. Conclusions The absence of face mask mandates underline individual autonomy but may also suppress personal responsibility due to social influence. Face masks are only temporarily acceptable in liberal Western societies and face mask mandates should be enforced only when epidemiologically necessary.